Chemical defense of the eastern newt (Notophthalmus viridescens): variation in efficiency against different consumers and in different habitats. - Zachary H Marion (Public Library of Science (PLoS), 2011)
Amphibian secondary metabolites are well known chemically, but their ecological functions are poorly understood--even for well-studied species. For example, the eastern newt (Notophthalmus viridescens) is a well known secretor of tetrodotoxin (TTX), with this compound hypothesized to facilitate this salamander's coexistence with a variety of aquatic consumers across the eastern United States. However, this assumption of chemical defense is primarily based on observational data with low replication against only a few predator types. Therefore, we tested the hypothesis that N. viridescens is chemically defended against co-occurring fishes, invertebrates, and amphibian generalist predators and that this defense confers high survivorship when newts are transplanted into both fish-containing and fishless habitats. We found that adult eastern newts were unpalatable to predatory fishes (Micropterus salmoides, Lepomis macrochirus) and a crayfish (Procambarus clarkii), but were readily consumed by bullfrogs (Lithobates catesbeianus). The eggs and neonate larvae were also unpalatable to fish (L. macrochirus). Bioassay-guided fractionation confirmed that deterrence is chemical and that ecologically relevant concentrations of TTX would deter feeding. Despite predatory fishes rejecting eastern newts in laboratory assays, field experiments demonstrated that tethered newts suffered high rates of predation in fish-containing ponds. We suggest that this may be due to predation by amphibians (frogs) and reptiles (turtles) that co-occur with fishes rather than from fishes directly. Fishes suppress invertebrate consumers that prey on bullfrog larvae, leading to higher bullfrog densities in fish containing ponds and thus considerable consumption of newts due to bullfrog tolerance of newt chemical defenses. Amphibian chemical defenses, and consumer responses to them, may be more complex and indirect than previously appreciated.